Intraoperative pulmonary function dynamics in adolescents undergoing reduction mammoplasty: A prospective case series. Issue 4 (December 2015) - Wiser, Itay; Mahon, Krity; Yaniv, Shirley; Mha, Ella Ziv; Carmel, Narin Nard; Heller, Lior
Background: Improvement of lung function following reduction mammoplasty has been previously reported among adult populations in the medical literature. Objectives: To evaluate the intraoperative dynamics of pulmonary function in adolescents undergoing reduction mammoplasty. Methods: The present study is a prospective case series of female patients 13 to 18 years of age who underwent inferior pedicle reduction mammoplasty between November 20, 2006 and April 4, 2011. Documented variables included patient baseline characteristics, operation duration, muscle relaxant use and total breast tissue removed. Intraoperative pulmonary function data documented included: tidal volume, respiratory rate, peak inspiratory pressure, positive end-expiratory pressure, oxygen saturation percentage and pulmonary compliance. Differences in pulmonary function data were calculated as ratio between final and initial intraoperative values. Results: Twenty-six patients were included in the analysis. Mean (± SD) age was 16.9±1.1 years and mean body mass index was 28.9±6.1 kg/m 2 . Mean operation time was 218±52 min, with average total bilateral breast tissue removal of 1810±1065 g. Improvement in lung compliance was observed in 24 patients (92.3%; P<0.0001). Mean intraoperative lung compliance improvement was 23.92% (95% CI 8.3% to 37%; P=0.001). Conclusion: Intraoperative improvement in lung compliance was observed in adolescent patients undergoing reduction mammoplasty.